Intensity of Social Media Use and Literacy Skills in Students: A Study in the Context of Learning, Entertainment, and Communication - Ilham, Ilham; Siti Rohmani (Global Synthesis in Education Journal, 2024)
This research scrutinizes the correlation between social media usage intensity and literacy skills among 397 high school and vocational students in Indonesia, focusing on learning, entertainment, and communication. Utilizing a descriptive quantitative approach, the study categorizes social media usage. It evaluates literacy skills, revealing a significant correlation between learning and communication but no impact on entertainment. The confirmed homoskedasticity of the regression model strengthens the findings. This suggests implications for educational strategies and advances our understanding of how social media affects literacy. Future studies should broaden samples, consider diverse demographics, and employ comprehensive designs for nuanced findings—tailored interventions to enhance social media usage and support literacy warrant further exploration.